Weightlifting elite's power snatch technique - Khasin, L. A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze and improve the power snatch techniques applied by the modern elite weight-lifters.Methods and structure of the study. Special studies at Moscow State Academy of Physical Culture in 2010-2020 showed that the modern elite weightlifter`s power snatch technique excellence research and the relevant individual pro-gress recommendations need to be based on analyses of the individual weightlifting technique micro-structuring studies - that require modern expertise and technologies. Since 2006 our research team has analyzed sports techniques using a high-speed video capturing toolkit, analysis of the reference literature, mathematical modeling tools, digital filters and modern software packages Matlab, Tema, MaxTraq, etc. The study was designed to: (1) Analyze the relevant theoretical and practical literature; (2) Make high-speed video captures (by a single of few cameras including the synchronized ones) to analyze some 100-plus snatches in the elite weightlifting trainings and top-ranking competitions including the World and European championships; (3) Select the most informative execution elements and indices; (4) Analyze the power snatch technique biomechanics; (5) Describe the best power snatch technique of the elite weightlifters; and (6) Come up with practical power snatch technique improvement recommendations. Results and conclusion. Our power snatch technique phasing analysis showed benefits of the following execution sequence for the weightlifting elite: toes-standing in the acceleration phase with a powerful push on the weight. We would also recommend a focused training of the aerial phase in the power snatch technique with a special attention to the arms straightening in the elbow and shoulder joints.